Promoting communication skills for information systems students in Australian and Portuguese higher education : action research study - Isaias, Pedro (2015)
This paper aims to examine the value of communication skills learn- ing process through various assessments in Information Systems (IS) postgrad- uate units in Australia and Portugal. Currently, communication skills are indispensable to students in expanding their social networks and their knowl- edge at university and in the future workplace, since businesses expect their employees to have strong communication and presentation skills. This paper provides empirical evidence based on the anonymous quantitative and qualita- tive data collected during 2 years from 126 postgraduate students, which were collected via formal and informal feedback. Various assessment methods were used in Information Systems units to promote and develop the communication skills; these assessments are: reflective journal, business plan and prototype, discussion forum, presentation, and final examination. A Communication skills model (CSM) was developed based on Action research principles to promote the assessments which will assist IS students to enhance their communication skills. The research outcomes indicated that integrating communication skills in the assessments will allow students to promote their communication skills and boost their self-esteem skills. Furthermore, this paper added a new theoretical and practical contribution to higher-education teaching and learning literature, especially the action research for teachers to promote and develop communica- tion skills among students. Finally, integrating these skills in the units should meet the objectives and aims of the units, Master’s degrees, universities, and businesses’ needs, and satisfy our student’s needs